Using sewage sludge as a permeable reactive barrier for remediation of groundwater contaminated with lead and phenol. Issue 4 (4th March 2017) - Faisal, Ayad A. H.; Abd Ali, Ziad T.
ABSTRACT: We investigated the efficiency of granular dead anaerobic sludge (GDAS) biosorbent as a permeable reactive barrier for remediation of groundwater contaminated with lead–phenol (Pb-Ph) present simultaneously. Batch tests were performed to characterize the equilibrium sorption properties of the GDAS and sandy soil in the Pb-Ph containing aqueous solutions. Computer solutions (COMSOL) Multiphysics 3.5a software was used for simulating the two-dimensional equilibrium transport of lead–phenol including the sorption process through the saturated sandy soil in the presence of GDAS. A good agreement between the predicted and experimental results was recognized with the root-mean-squared error not exceeding 0.049.